Antidiabetic burdens among geriatric diabetic patients and its association with quality of life - Shalihin, Mohd Shaiful Ehsan (Kulliyyah of Allied Health Sciences, 2019)
Geriatric diabetic patients contribute to the major demographic background of diabetic patients follow up in primary health clinics. Despite their increasing age and morbidities, they are still targeted towards good sugar control achieving ideal HbA1c level, without taking into consideration of their quality of life. This study aims to determine the prevalence of antidiabetic usage among geriatric diabetic patients and their association with the patients quality of life. A cross-sectional study was done among 269 geriatric diabetic patients in all government health clinics in Kuantan using Diabetes Quality of Life questionnaire. SPSS version 23 is used for statistical analysis. Most of the geriatrics are female (61%), Malay (84.8%), pensioner (54.3%), education up to primary school (52%) and stay with family members (93.7%). In terms of antidiabetic agents, mostly depend on two antidiabetic agents (48%) followed by single antidiabetic agent (32%). 0.4% still taking glibenclamide despite its risk of hypoglycaemia. Usage of insulin is still common in the elderly in which 21% of them are on intermediate-acting insulin, 15.6% on premixed insulin and 7.8% on shortacting insulin. Interestingly, those taking a higher number of antidiabetic agents are associated with higher DQOL score (p = 0.03) compared to those taking one or two antidiabetic medications. Those taking long-acting insulin also significantly have higher DQOL score (0.037). Despite the risk of polypharmacy, geriatric patients do benefit the better quality of life with the further intensification of their antidiabetic medications according to guidelines. Usage of long-acting